2014
DOI: 10.18052/www.scipress.com/ilcpa.26.1
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Antifungal, Anti-Oxidant, Anti-Inflammatory and Anti-Hypertensive Activities of N-Chloropyrazinamide

Abstract: N-chloropyrazinamide was prepared by the chlorination of pyrazinamide using trichloroisocyanuric acid. The experimental results ascertained that the tested N-chloropyrazinamide showed good antimicrobial activities when compared to standard drug. It was found that Nchloropyrazinamide at different concentrations exhibited significant dose dependent anti-oxidant, anti-inflammatory and anti-hypertensive activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Literature survey showed that when both hydrogen and chloride ions were found to catalyze the reactions involving N-halo compounds, molecular chlorine was assumed to act as the effective oxidant and such reports were given in the oxidation of chalcones [17] and aminoacids [18]. At the lower pH, molecular chlorine is the much more reactive species than hypochlorous acid [19].…”
Section: Resultsmentioning
confidence: 99%
“…Literature survey showed that when both hydrogen and chloride ions were found to catalyze the reactions involving N-halo compounds, molecular chlorine was assumed to act as the effective oxidant and such reports were given in the oxidation of chalcones [17] and aminoacids [18]. At the lower pH, molecular chlorine is the much more reactive species than hypochlorous acid [19].…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids were purchased from Merck and used as such. N-chloropyrazinamide 23 was prepared by chlorinating pyrazinamide using trichloroisocyanuric acid (TCICA). Standard solution of NCPZA was prepared afresh.…”
Section: Methodsmentioning
confidence: 99%
“…Although a lot of works have been reported on the oxidation of amino acids by N-halo compounds [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] , the kinetic investigation on the oxidation of amino acids by N-chloropyrazinamide, a newly synthesized oxidant 23 , is not reported so far. Hence, in the present investigation, the kinetics of oxidation of alanine (Ala), glycine (Gly), leucine (Leu), phenyl alanine (Phe) and valine (Val) with N-chloropyrazinamide (NCPZA) in aqueous acetic acid medium in the presence of perchloric acid has been reported 26 .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In recent development NCS has been extensively employed as an oxidant for a variety of organic substrates, [3] chalcones, [4] 2-hydroxy propanoic acid [5] (in alkaline medium) 9-telluraheptadecanoic acid, [6] alcohols, [7] benzyl phenyl ether [8] etc.…”
Section: Introductionmentioning
confidence: 99%